Perímetro e área: uma engenharia didática utilizando o GeoGebra sob o olhar das representações semióticas - Assumpção, Paula Gabrieli Santos de (2015)
This paper aims answering the following question: Can a dynamic approach contribute to the geometry s teaching and learning process for 7th grade students in the fundamental school, concerning the concepts of perimeter and polygons area, taking into consideration the theory of semiotic representation records? In order to do this, it was elaborated, implemented and evaluated a sequence of activities in the GeoGebra software from the theoretical subsides found in the semiotic representation records theory, according to Duval (2003, 2005, 2009, 2011, 2012a, 2012b, 2013). The didactic experiment was accomplished with two groups of 7th grade students from fundamental school in a public state school in the city of Toropi, RS. This research was organized following the guidelines of the didactic engineering methodology, according to Artigue (1996). Based on the analysis of results when putting into practice the sequence of activities it was verified the students could learn the concepts of perimeter and polygons area in a dynamic environment under the view of the semiotic representation records theory. It was also recognized as fundamental to develop the steps in the didactic engineering the considerations brought by this theory. Besides, it was considered satisfactory the functionalities of the GeoGebra software since it was an intermediary tool, helping in the process of seeing the subjects of research, when solving activities with emphasis in image records. It was seen in the development of activities an improvement of their visual processes in relation to the heuristic examination of the geometrical figures. Allowing them a better perception of the way they elucidate the geometric representations involved.